EVALUATION OF TRANSAMINASE ACTIVITIES IN PATIENTS WITH DIABETIC NEPHROPATHY (Journal of Biomedical Investigation, 2025)
Background: Nephrotic syndrome and widespread glomerulosclerosis are the hallmarks of diabetic nephropathy, a progressive kidney disease brought on by angiopathy of capillaries in the kidney glomeruli. Aim: Thhis study aimed to assess the activity of transaminases, specifically alanine aminotransferase (ALT) and aspartate aminotransferase (AST), in patients with diabetic nephropathy. Materials and Methods: Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activity were measured in patients with diabetic nephropathy, diabetes mellitus (without nephropathy), and control participants who appeared to be in good health. A total of 150 participants were involved in this study. Three groups of 50 patients each who had diabetes mellitus, diabetic nephropathy, and control subjects who appeared to be in good health. The Reitman and Frankel technique of analysis was used to measure ALT and AST activity. Results: Diabetic nephropathy was associated with a substantial increase in enzyme activity above the control value (P0.05)], diabetes mellitus was also associated with a little increase in AST activity above the control value. Patients with diabetic nephropathy had mean ALT and AST activity that was statistically significant (P
Keywords: diabetic nephropathy; Alanine aminotransferase; diabetes mellitus